The chemical properties of healthy drink from Pedada fruit (Sonneratia caseolaris) with natural dyes of Roselle (Hibiscus sadbariffa L.) and Beetroot (Beta vulgaris L.) - Meyci Trisna; Edi Kurniawan; Nina Hartati; Rajiyatul Muzni; Nagita Audya Agnes S; Tiara Andriani (CV Edujavare Publishing, 2026)
Mangrove plants play an important role in maintaining the balance of coastal ecosystems and also produce pedada fruit (Sonneratia caseolaris), which has the potential as a functional food ingredient. However, the use of pedada fruit as a healthy beverage product is still relatively limited. This study aims to develop a healthy beverage based on pedada fruit and analyze the chemical characteristics and safety of the product. The innovation process was carried out by making pedada fruit juice with the addition of roselle flowers and beetroot to improve taste and functional value. Parameters analyzed included temperature, pH, formole number, and arsenic (As) contamination content. The results showed that the resulting drink had a temperature of 33.5°C and a pH of 4.1. The addition of roselle flowers and beetroot contributed to a decrease in pH so that it was within the appropriate acidic range for fruit juice drinks, which is below 4.5, which supports the microbiological safety of the product. The formole number analysis showed an average value of 154, well above the minimum SNI standard of 15, indicating adequate free amino acid content and product quality that was maintained during the production and storage process. Testing for arsenic contamination yielded a concentration of 0.018 mg/kg, lower than the Indonesian National Standard (SNI) maximum limit of 0.1 mg/L. Therefore, the developed pedada fruit juice has good chemical quality, adequate nutritional value, and is safe for consumption.